AB0912 Subclinical Hypovitaminosis D and Osteoporosis in Breast Cancer Patients. (9th June 2015) - Gheita, T.A.; Sayed, S.; Hammam, W.; Hegazy, G.
Abstract : Background: Vitamin D may play a role in breast cancer prevention. While the association between Vitamin D and breast cancer risk/prognosis is still controversial, a high proportion of women at-risk for breast cancer or affected by the disease have deficient vitamin D levels. Objectives: This study was designed to detect the incidence of osteoporosis and circulating concentration of 25-hydroxy vitamin D level in breast cancer patients as well as their relation to the treatment received and to stage of breast cancer. Methods: Seventy-four female patients with breast cancer were included in the study; their mean age was 47.89±9.59years. Another fifty-two age and sex matched subjects were included as control. All patients were receiving chemotherapy, 40 received hormonal therapy, 50 radiotherapy and 10 surgically removed. Vitamin D level and dual energy x-ray absorptiometry (DXA) were performed for patients and control Results: Vitamin D level was significantly higher in the control (23.66±5.2 IU/L) than in patients (18.37±6.25 IU/L) (p<0.0001). There was a tendency to a normal DXA score in the forearm of the patients while the score of the hip and spine were significantly different from that of the control (p=0.001 and p=0.034 respectively). In patients, there were significant correlations between 25(OH)D3 and hip DXA (r=0.25, p=0.03), and significant negative correlations between tumor grades and DXA of hip, forearm and spine (r= -0.42, r=-0.39, r=-0.45 respectively; p<0.0001). Conclusions: Our finding support low serum vitamin D concentration in breast cancer patients. In addition, their BMD of the hip is obviously reduced. The sub-clinically detected hypovitaminosis D and osteoporosis throw light on the importance of offering calcium and vitamin D supplements to breast cancer patients. It is further recommended that breast cancer patients have a DXA scan performed at baseline and repeatedly on a yearly basis. Disclosure of Interest: None declared